RESTORATIF JUSTICE SEBAGAI WUJUD PELAKSANAAN AZAS ULTIMUM REMIDIUM DI DALAM TINDAK PIDANA PERPAJAKAN - Rudy Gunawan Bastari; Femmy Silaswaty Faried, Amir Djunaidi (PROSEDING, 2022)
The regulation of taxation in Indonesia, is to have the aim of being an instrument and legal basis in tax collection, to increase state revenues. The state, in this case the government, with all the policies that form the basis for the collection, is to make a breakthrough and also an effort that can provide prosperity for the state and its citizens. Of course, in the tax law setting which is based on the Law on General Provisions of Taxation and also the Law on the Harmonization of Tax Regulations, in addition to regulating taxation procedures, it also regulates the sanctions imposed on taxpayers who do not fulfill their obligations which report taxes and pay them. This research was conducted using a normative method, by examining the regulations that form the basis for setting footing. The purpose of this study is to provide a clear regulation on the concept of tax criminal law enforcement with the concept of restorative justice which also fulfills the Ultimum remidium principle as it is known in criminal law. By using several theoretical foundations from the notion of understanding contained in the legislation and also the opinions of legal experts. Keywords: Restorative Justice, Ultimum Remedium, Tax